Cooperation Between State Agencies and NGOs in Crisis Situations - Dariusz Szydłowski; Kamil Martyniak (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The Police as the largest uniformed law enforcement agency in Poland (more than 100,000 functionaries) with strictly hierarchical command structure is capable of entering into cooperation with external entities including non-governmental organizations. NGOs are all entities which are not public administration organs or units and which operate on a non-profit basis. A characteristic feature of an NGO is the lack of links to the public authorities. In Poland the status of NGOs is regulated by the Public Benefit and Volunteer Work Act of 2003 which introduced an extended definition of non-governmental organizations as entities engaged in public interest and charitable activities (ngo.pl, 2018). The paper presents the subject matter related to the cooperation of the Polish Police with non-governmental organizations with respect to their statutory tasks, determines the place of NGOs in the security system and draws conclusions and recommendations regarding the cooperation.